Radioiodine treatment of feline hyperthyroidism in Germany - Puille, M.; Knietsch, M.; Spillmann, T.; Grünbaum, E.-G.; Bauer, R. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Establishment of radioiodine treatment of feline hyperthyroidism in veterinary routine in accordance with German radiation protection regulations. Patients and methods: 35 cats with proven hyperthyroidism were treated with 131I in a special ward. Thyroid uptake and effective halflife were determined using gammacamera dosimetry. Patients were released when measured whole body activity was below the limit defined in the German “Strahlenschutzverordnung”. Results: 17/20 cats treated with 150 MBq radioiodine and 15/15 cats treated with 250 MBq had normal thyroid function after therapy, normal values for FT3 and FT4 were reached after two and normal TSH levels after three weeks. In 14 cats normal thyroid function was confirmed by controls 3-6 months later. Thyroidal iodine uptake was 24 ± 10%, effective halflife 2.5 ± 0.7 days. Whole body activity <1 MBq was reached 13 ± 4 days after application of 131I. Radiation exposure of cat owners was estimated as 1.97 Sv/MBq for adults. Conclusion: Radioiodine therapy of feline hyper-thyroidism is highly effective and safe. It can easily be performed in accordance with German radiation protection regulations, although this requires hospitalisation for approximately two weeks. Practical considerations on radiation exposure of cat owners do not justify this long interval. Regulations for the veterinary use of radioactive substances similar to existing regulations for medical use in humans are higly desirable.
Keywords: Cat; hyperthyroidism; radioiodine therapy; radiation safety